Analysis of the Implementation of Good Corporate Governance Principles in Increasing Lending - Budi Andriani (Advances in Management & Financial Reporting, 2023)
This study aims to assess the level of efficiency and effectiveness of the credit department, especially in terms of lending, and to obtain an overview of the principles and principles of good corporate governance in the company's lending procedures. The population in this study were all employees at the Main Branch Office (KCU) Panakukang PT. Bank Central Asia (Persero) Tbk Makassar. The research sample was selected based on specific considerations or criteria from the researcher to get as much information as possible. The source of data in this study is primary data obtained through field research, using data collection techniques in questionnaires and interviews. This research was processed using qualitative analysis techniques—the steps taken by analyzing data reduction, presentation, and concluding. The study results indicate that the implementation of the principles of Good Corporate Governance by Bank BCA has been running very well, which can be seen from the fulfillment of all the principles of Good Corporate Governance in the operations of Bank BCA, especially in terms of lending procedures. This has increased the number of loans and led to a decrease in the ratio of non-performing loans over the last six years